Shoulder Arthroscopy Does Not Adequately Visualize Pathology of the Long Head of Biceps Tendon. Issue 1 (8th January 2016) - Saithna, Adnan; Longo, Alison; Leiter, Jeff; Old, Jason; MacDonald, Peter M.
Background: Pulling the long head of the biceps tendon into the joint at arthroscopy is a common method for evaluation of tendinopathic lesions. However, the rate of missed diagnoses when using this technique is reported to be as high as 30% to 50%. Hypothesis: Tendon excursion achieved using a standard arthroscopic probe does not allow adequate visualization of extra-articular sites of predilection of tendinopathy. Study Design: Descriptive laboratory study. Methods: Seven forequarter amputation cadaveric specimens were evaluated. The biceps tendon was tagged to mark the intra-articular length and the maximum excursions achieved using a probe and a grasper in both beach-chair and lateral positions. Statistical analyses were performed using analysis of variance to compare means. Results: The mean intra-articular and extra-articular lengths of the tendons were 23.9 and 82.3 mm, respectively. The length of tendon that could be visualized by pulling it into the joint with a probe through the anterior midglenoid portal was not significantly different when using either lateral decubitus (mean ± SD, 29.9 ± 3.89 mm; 95% CI, 25.7-34 mm) or beach-chair positions (32.7 ± 4.23 mm; 95% CI, 28.6-36.8 mm). The maximum length of the overall tendon visualized in any specimen using a standard technique was 37 mm. Although there was a trend to greater excursion using a grasper through the same portal, this was not statistically significant. However, using a grasper through the anterosuperior portal gave a significantly greater mean excursion than any other technique (46.7 ± 4.31 mm; 95% CI, 42.6-50.8 mm), but this still failed to allow evaluation of Denard zone C. Conclusion: Pulling the tendon into the joint with a probe via an anterior portal does not allow visualization of distal sites of predilection of pathology. Surgeons should be aware that this technique is inadequate and can result in missed diagnoses. Clinical Relevance: This study demonstrates that glenohumeral arthroscopy does not allow visualization of common areas of pathology of the long head of the biceps tendon.